The Making of Italy, 1796–1866 - Mack Smith, Denis. author. aut Link
XIV, 428 p.
Keywords: First published in 1968, this standard text on Italian nineteenth-century history is reissued, with a new preface, in hardcover and paperback, to meet a continuing demand.